Spatial nonlinear optics for securing information - Chen, Wen (Light, science & applications, 2022)
The high degrees of freedom of light, various optical structures and optical materials can be explored and applied to develop optical encryption for securing information. An exciting optical image encryption approach has been proposed based on spatial nonlinear optics.